Rancang Bangun Sistem Informasi Pendistribusian Barang Movement Regional pada Perum BULOG DIVRE Jawa Timur - Rosdiyaningsih, Fitriyah; Utama, I Gede Arya; Prasetiya, Hendro Poerbo (Jurnal JSIKA, 2012)
In order to maintain the resilience of the stock of rice which is flattened on the regional division/Sub regional division Perum BULOG required equity stock from surplus areas to deficit areas corresponding to the number and needs with good conditions. Perum BULOG as the State-Owned Enterprises through the activities of public service assigned to the regional activities undertaken movement. The processing of the data movement is still simple that regional is very difficult to do the checking of the resilience of the stock items in the warehouse, it will lead to constraints on the distribution of the activities of the regional movement into a slow, this is because not having the information system supporting the activities of the movement in the Perum BULOG Regional Division East Java. Designed to wake up the system of information on Regional distribution of the goods Movement Perum BULOG Regional Division East Java will help create regional governance process movement an efficient, competitive and accountable. The method used is the regional activities of the movement of transport method, use methods of the cost of the smallest (Least Cost) and Modified Distribution (MODI). Using these methods in this final paper gave the total cost of transporting it to a minimum in order to help deliver a decision in the distribution of goods that are optimal for doing the activities of the regional movement on Perum BULOG Regional Division East Java.   Keyword: distribution, freight, transportation, bulog